Resource Niches of Co-occurring Invertebrate Species at an Offshore Wind Turbine Indicate a Substantial Degree of Trophic Plasticity - Mavraki, Ninon; De Mesel, Ilse; Degraer, Steven; Moens, Tom; Vanaverbeke, Jan (Frontiers in Marine Science, 2020)
Offshore wind farms in the North Sea are proliferating, causing alterations in local ecosystems by adding artificial hard substrates into naturally soft-bottom areas. These substrates are densely colonized by fouling organisms, which may compete for the available resources. While the distribution of some species is restricted to specific parts of the turbine, others occur across depth zones and may therefore face different competitive environments. Here we investigate the trophic niches of seven invertebrate species: three sessile (Diadumene cincta, Metridium senile and Mytilus edulis), one hemi-sessile (Jassa herdmani) and three mobile species (Ophiothrix fragilis, Necora puber and Pisidia longicornis) that occur in multiple depth zones. We hypothesized that these species would be trophic generalists, exhibiting trophic plasticity by selecting different resources in different depth zones, to cope with the different competitive environments in which they occur. We analyzed δ13C and δ15N of these species and their potential resources across depth zones. Our results show that most of these invertebrates are indeed trophic generalists which display substantial trophic plasticity, selecting different resources in different zones. Degree of trophic plasticity was not related to mobility of the species. There are two possible explanations for these dietary changes with depth: either consumers switch diet to avoid competition with other (dominant) species, or they benefit from the consumption of a non-limiting resource. Only Diadumene cincta was a trophic specialist that consumed suspended particulate organic matter independent of its zone of occurrence. Altogether, trophic plasticity appears an important mechanism for the co-existence of invertebrate species along the depth gradient of an offshore wind turbine.